Achmea Between the Orthodoxy of the Court of Justice and Its Multi-faceted Implications: An Introduction - Ségolène Barbou des Places; Emanuele Cimiotta; Juan Santos Vara (European Papers, 2019)
(Series Information) European Papers - A Journal on Law and Integration, 2019 4(1), 7-17 | Article | (Table of Contents) I. Introduction. - II. Achmea, from the perspective of international investment law specialists. - III. An impressive set of consequences inferred from Achmea. - IV. Achmea and the European integration process. | (Abstract) The Achmea case has generated much controversy and fierce criticism from investment lawyers and international law specialists. This Special Section takes such reaction as an invitation to investigate the premises and the impressive set of consequences inferred from the judgment, both for investment arbitration and the European integration process. But the Achmea judgment is not only about how EU law interacts with international investment law. The Court of Justice also deals with the constitutional foundations of the EU integration and strives to protect the European model of justice, organized as a system, from disintegrative forces.